Associations between maternal scaffolding and executive functioning in 3 and 4year olds born very low birth weight and normal birth weight - Lowe, Jean (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2014)
Deficits in executive function, including measures of working memory, inhibition and cognitive flexibility, have been documented in preschoolers born very low birth weight (VLBW) compared with preschoolers born normal birth weight (NBW). Maternal verbal scaffolding has been associated with positive outcomes for both at-risk and typically developing preschoolers.